Erratum: Yuan, M.D. & Wang, R.J. (2020) Involucrella lithophila (Rubiaceae: Spermacoceae): A new species from Guangxi, China. Phytotaxa 464 (1): 59–68. - Yuan, Ming-Deng; Wang, Rui-Jiang (Phytotaxa, 2021)
N/A